2013
DOI: 10.2174/15680266113136660203
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the Histidine Pathway in Mycobacterium tuberculosis

Abstract: Worldwide, tuberculosis is the leading cause of morbidity and mortality due to a single bacterial pathogen, Mycobacterium tuberculosis (Mtb). The increasing prevalence of this disease, the emergence of multi-, extensively, and totally drug-resistant strains, complicated by co-infection with the human immunodeficiency virus, and the length of tuberculosis chemotherapy have led to an urgent and continued need for the development of new and more effective antitubercular drugs. Within this context, the L-histidine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 131 publications
0
23
0
1
Order By: Relevance
“…Another top ranking pathway is the one responsible for histidine biosynthesis, which has been suggested as harboring potential drug targets due to its absence in mammals [62]. The pathway is composed by eight essential proteins.…”
Section: Construction and Incorporation Of Mtb Metabolic Network Analmentioning
confidence: 99%
“…Another top ranking pathway is the one responsible for histidine biosynthesis, which has been suggested as harboring potential drug targets due to its absence in mammals [62]. The pathway is composed by eight essential proteins.…”
Section: Construction and Incorporation Of Mtb Metabolic Network Analmentioning
confidence: 99%
“…ATP‐PRT acts as the gateway into His biosynthesis and as such plays an important metabolic role. It has been the focus of several studies and identified as a potential target of new antibiotic therapies . The nature of the active species in solution of the long form of this enzyme and the details of allostery have been unclear; with early solution studies favoring a change in quaternary structure from active dimer to inactive His‐bound oligomer .…”
Section: Discussionmentioning
confidence: 99%
“…It has been the focus of several studies and identified as a potential target of new antibiotic therapies. 26,27 The nature of the active species in solution of the long form of this enzyme and the details of allostery have been unclear; with early solution studies favoring a change in quaternary structure from active dimer to inactive His-bound oligomer. 21,22 The loose hexameric structure observed in the absence of His for the MtuATP-PRT and EcoATP-PRT was interpreted as consistent with an inactive hexamer.…”
Section: Discussionmentioning
confidence: 99%
“…The domain possessing the phosphatase activity was conserved within the bifunctional HisB of modern bacterial clades such as Gammaproteobacteria (Escherichia and Salmonella), whereas in clades such as Actinomycetales (Mycobacteria, Corynebacterium, and Streptomyces), the phosphatase activity was performed by a unique monofunctional enzyme. Interestingly, Rv0114, which is annotated as a D-glycero-␣-D-mannoheptose 1,7-bisphosphate phosphatase (gmhB) (17), also speculated to be a probable HolPase (18) has diverged separately from both the bifunctional HisB and monofunctional HisN, suggesting a possibly different role of this protein other than that of a HolPase (Fig. 1A).…”
Section: Rv3137 Is the Mtb Holpase And Not An Impasementioning
confidence: 99%